Post-Acute Sequelae of COVID-19 and Cardiovascular Autonomic Dysfunction: What Do We Know? - Giandomenico Bisaccia (MDPI AG, 2021)
Post-acute sequelae of SARS-CoV-2 (PASC), or long COVID syndrome, is emerging as a major health issue in patients with previous SARS-CoV-2 infection. Symptoms commonly experienced by patients include fatigue, palpitations, chest pain, dyspnea, reduced exercise tolerance, and “brain fog”. Additionally, symptoms of orthostatic intolerance and syncope suggest the involvement of the autonomic nervous system. Signs of cardiovascular autonomic dysfunction appear to be common in PASC and are similar to those observed in postural orthostatic tachycardia syndrome and inappropriate sinus tachycardia. In this review, we report on the epidemiology of PASC, discuss current evidence and possible mechanisms underpinning the dysregulation of the autonomic nervous system, and suggest nonpharmacological and pharmacological interventions to treat and relieve symptoms of PASC-associated dysautonomia.